1999
DOI: 10.1118/1.598727
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of the imaging performance of metal plate/phosphor screens used in radiotherapy

Abstract: The imaging performance of metal plate/phosphor screens which are used for the creation of portal images in radiotherapy is investigated by using Monte Carlo simulations. To this end the modulation transfer function, the noise power spectrum and the detective quantum efficiency [DQE(f)] are calculated for different metals and phosphors and different thicknesses of metal and phosphor for a range of spatial resolutions. The interaction of x-rays with the metal plate/phosphor screen is modeled with the EGS4 elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 27 publications
1
68
0
Order By: Relevance
“…(The performance of MV imaging systems operated in the absence of an overlying metal plate has been previously examined.) 35,36 Also note that a reflector with negligible radiation attenuation was introduced to provide desirable optical properties and was modeled in the simulation with a zero mass attenuation coefficient for traversing x rays. Two extreme cases for the reflector were examined: one with 100% absorptivity and 0% reflectivity (referred to as "black"), and the other with 0% absorptivity and 100% reflectivity (referred to as "mirror").…”
Section: A Converter Designs Examined In the Studymentioning
confidence: 99%
“…(The performance of MV imaging systems operated in the absence of an overlying metal plate has been previously examined.) 35,36 Also note that a reflector with negligible radiation attenuation was introduced to provide desirable optical properties and was modeled in the simulation with a zero mass attenuation coefficient for traversing x rays. Two extreme cases for the reflector were examined: one with 100% absorptivity and 0% reflectivity (referred to as "black"), and the other with 0% absorptivity and 100% reflectivity (referred to as "mirror").…”
Section: A Converter Designs Examined In the Studymentioning
confidence: 99%
“…Kihlén et al ( 16 ) reported that a metal with an atomic number around 26–29 would be an optimal material for a metal screen with regard to quality after measuring the scattered to primary dose ratio. On the other hand, Kausch et al ( 17 ) reported that metals with a high atomic number perform better than lighter metals in maximizing the detective quantum efficiency using Monte Carlo simulation. In the future, investigation of the optimal thickness or material of a filter to be used would further improve the image quality of both standard and bone‐enhanced portal images.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate stages 1-3, a Monte-Carlo model is used, similar to that used by Kausch et al [7]. X-ray absorption probabilities are generated using the EGSnrc software [8].…”
Section: Modeling Methodsmentioning
confidence: 99%